Factors Influencing the Supply Chain of Muslimas Fashion (Hijabs) on Brand Loyalty - Rozita Naina Mohamed; Bahtiar Mohamad; Norzehan Abu Bakar (International Journal of Supply Chain Management, 2019)
Fashion must have value and purpose and truly resonate to the consumer. Strong brands with consistent powerful messages can create loyalty and a sense of worth that transcends the burden of choice. Therefore, this study is carried out to identify the factors that influenced brand loyalty towards supply chain of Muslimas fashion (Hijabs) in Malaysia. Based on a review of the existing literature in a range of fields, this study proposes that brand loyalty indicates the importance of brand name, product quality, price, store environment, promotion, service quality and style. The success of a firm depends largely on the factors that influencing the supply chain and its capability to attract consumers towards its brands. A quantitative methodology was used in this study. 400 respondents of Muslimas fashion customers in Shah Alam were used to gather information about their perception on the brand loyalty towards supply chain of Muslimas fashion. The research results showed that there is a significant relationship between factors of brand loyalty (price, promotion, service quality, store environment, and style) with Muslimas fashion brand loyalty.